Bonding, bridging and linking social capital and psychological empowerment among squatter settlements in Tehran, Iran - Babaei, Hamidreza; Ahmad, Nobaya; Gill, Sarjit S. (TextRoad Publication, 2012)
This study aims to determine the effect of bonding, bridging and linking social capital in the psychological empowerment among squatter settlements in Tehran, Iran. The sample comprised 328 poor people in two communities from Iran, which were randomly selected for the study. A self-administered questionnaire was used as the data collection method and the stratified random sampling technique was employed. The results revealed the significant effect of bonding, bridging and linking social capital on psychological empowerment among squatter settlements. Bonding social capital had the largest beta coefficient than other dimensions, such as bridging and linking social capital in predicting psychological empowerment among squatter settlements.